Experiment on Strength and Failure Behavior of Sandstone Containing Pre-Existing Cracks Under Brazilian Compression - Cao, Xiaojian; Zhang, Han; Yu, Jun; Yu, Tianchong; Qing, Yuxing (Frontiers in Physics, 2021)
Determination the mechanical properties of rock containing pre-existing crack under tension condition is of great significance to understand the failure process of rock in engineering. This paper presents the experimental results of sandstone containing pre-existing crack under Brazilian compression. The characteristics of the microcracks were analyzed by scanning electron microscope (SEM), The results show that the rock containing pre-existing crack has obvious anisotropy in mechanical properties. When the crack inclination is 45°, the rock has the minimum tensile strength and the weakest axial deformation resistance.